Global Optimization and Control of Greenhouse Climate Setpoints for Energy Saving and Crop Yield Increase - Yuanping Su; Lihong Xu (Agriculture)
The greenhouse climate setpoint is an important factor that can affect the energy consumption of greenhouse climate regulation. Therefore, optimising the setpoint is an effective way to save energy. This work proposes a novel global optimization and control approach for the greenhouse climate setpoint. In the proposed method, an interpolation control method is used to simulate the entire control process in order to evaluate the energy consumption and crop yield. Based on the estimated energy consumption and crop yield samples, a surrogate-based global optimisation approach is introduced to find the optimal setpoints of the greenhouse climate. In contrast to the steady-state global optimisation of the setpoint, the proposed dynamic global optimisation can save energy by 27%, and the crop yield can be improved by 25%. The optimisation results indicate that the prices of CO2 and crop products can significantly influence the setpoints of CO2 concentration and temperature inside the greenhouse. In the considered simulation case, when the selling price of a crop product is lower than 10 CNY/kg, the total profit is negative, the setpoint of CO2 concentration reaches the lower bound, and the temperature setpoint is only 13.05 °C.